Spectral properties of the two-dimensional multiwell potential - Chekanov, N.A.; Shevchenko, E.V. (Вопросы атомной науки и техники, 2007)
Two-dimensional multiwell Hamiltonian system with four local minima is considered. The motion of the system shifts from regular to chaotic through “mixed state”, i.e. the state, when regular and irregular regimes of motion coexist in different local minima. Three regimes of motion – regular ( R), mixed state (RC), and chaotic (C) – are considered. For each energy region the spectrum is calculated by direct diagonalization in polar coordinates, the eigenstates are classified according to the irreducible representations of C3v -point group, and the spectral statistical properties are analyzed and compared to the theoretical predictions for integrable, chaotic and generic (neither regular nor chaotic) systems.